Batch Informed Trees (BIT*): Informed asymptotically optimal anytime search - Gammell, JD; Barfoot, TD; Srinivasa, SS (SAGE Publications, 2020)
Path planning in robotics often requires finding high-quality solutions to continuously valued and/or high-dimensional problems. These problems are challenging and most planning algorithms instead solve simplified approximations. Popular approximations include graphs and random samples, as used by informed graph-based searches and anytime sampling-based planners, respectively.